Tinjauan Terhadap Penyalahgunaan Dana dalam Yayasan Kemanusiaan: Studi Kasus pada Lembaga ACT - Jenniviera, Johana; Maryam, Salsabilla; Arief, Aisah Putri; Bestari, Qodri; Mahipal, Mahipal (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This research analyzes the Islamic perspective, legal outlook, media role, and humanitarian foundation's responsibility concerning cases of fund misappropriation, focusing on the controversy involving the Aksi Cepat Tanggap (ACT) Foundation in Indonesia. From an Islamic standpoint, corruption and fund misuse are considered serious violations of justice, honesty, and trustworthiness values. The Quran and Hadith provide guidance on the importance of transparency, integrity, and responsible fund management. Legally, fund misappropriation violates regulations governing fundraising and management, as seen in the ACT case, which exceeded government-permitted limits. Media also play a crucial role in highlighting fund misappropriation cases, framing them as ethical breaches and betrayals of trust. Finally, the humanitarian foundation's responsibility, particularly ACT, in adhering to laws and financial principles, comes under scrutiny, with assessments of the foundation's organizational involvement in fund management. In conclusion, fund misappropriation by humanitarian foundations is not just a legal issue but also threatens the integrity and public trust in humanitarian missions. Law enforcement, transparency, and good governance are key to addressing challenges of corruption and fund misuse in the humanitarian sector. Abstrak Penelitian ini menganalisis pandangan Islam, perspektif hukum, peran media, dan tanggung jawab yayasan kemanusiaan terhadap kasus penyelewengan dana, dengan fokus pada kontroversi yang melibatkan Yayasan Aksi Cepat Tanggap (ACT) di Indonesia. Dari sudut pandang Islam, korupsi dan penyalahgunaan dana dianggap sebagai pelanggaran serius terhadap nilai-nilai keadilan, kejujuran, dan amanah. Al-Qur'an dan hadis memberikan pedoman tentang pentingnya transparansi, integritas, dan pengelolaan yang bertanggung jawab terhadap dana. Dari segi hukum, penyalahgunaan dana melanggar peraturan yang mengatur pengumpulan dan pengelolaan dana, seperti yang terjadi dalam kasus ACT yang melebihi batas yang diizinkan oleh pemerintah. Media juga memainkan peran penting dalam menyoroti kasus penyelewengan dana, dengan framing yang menggambarkan pelanggaran etika dan kepercayaan. Terakhir, tanggung jawab yayasan kemanusiaan, khususnya ACT, dalam mematuhi undang-undang dan prinsip-prinsip keuangan menjadi sorotan utama, dengan penilaian terhadap keterlibatan organ yayasan dalam pengelolaan dana. Kesimpulannya, penyelewengan dana oleh yayasan kemanusiaan bukan hanya masalah hukum, tetapi juga mengancam integritas dan kepercayaan publik terhadap misi kemanusiaan. Penegakan hukum, transparansi, dan tata kelola yang baik menjadi kunci dalam mengatasi tantangan korupsi dan penyalahgunaan dana di sektor kemanusiaan.